Profesionalisme Guru Dalam Pembelajaran - Azhar, Sofia (Fakultas Adab dan Humaniora UIN Alauddin, 2013)
This journal discusses about the definition of teacherâs professionalism and the teaching, the terms of a professional teacher, the teacherâs performance, the ten qualities of the good teacher, the six of successful teacherâs characters, the unfortunate teacherâs character, the ten of teacherâs mistakes, the problem or difficulty of the teacher in learning